Power estimation at cutoff in a planar guide with small parabolic deformation - Choudhury P.K.; Shukla P.K.; Khastgir P.; Ojha S.P. (My University, 2025)
The present paper reports the analysis of the flow of power in a planar dielectric guide with its surfaces having very small parabolic deformation. Using the scalar wave approximation an eigenvalue equation for the flow of power in the core region has been derived which is then plotted against the dimensionless core parameter showing the variation of power flow in the main guiding region of the parabolic cylindrical waveguide.